Extraction and Characterization of Sugarcane Peel Wax. (25th July 2012) - Inarkar, Mangesh B.; Lele, S. S.
Abstract : Sugarcane peel is an agrowaste product and contains considerable amount of wax. This has a good technoeconomic potential. In view of this, the present study aims at extraction and characterization of wax from sugarcane peel. The yield of crude wax was 0.95% on dry weight basis. During Fourier transform-infrared spectroscopy (FT-IR) prominent peaks obtained at 2921.73 and 2851.64 (–CH), 1463.44 (–CH2), 1376.96 (–CH3), 1108.4 and 1170.16 (–C–O) 3395.60 (–OH), 1710.25 (–CHO), and 1736.63 (–COOH) indicate presence of alkanes, ketones, alcohols, aldehydes, and carboxylic acids, respectively. Alcohol and hydrocarbon fractions were also found by thin layer chromatography (TLC). Melting point of crude wax was observed to be 62.1°C. Molecular weight of wax was estimated to be 1706 Dalton. Composition of crude wax found using gas chromatography-mass spectroscopy (GC-MS) was alkanes (28.83%), ester (66.26%), fatty acids (4.58%), aldehyde (0.11%), and alcohol (0.22%).